Rol de la variante l83v de la oncoproteína e6 del virus papiloma humano tipo 16 en al transformación de las lesiones premalignas en malignas del cuello uterino - Vilela Desposorio, Carlos David (2011)
Since 1984, Trujillo recorded the highest incidence rates of cervical cancer in Peru. This situation was reason to be conducted this retrospective study in samples from patients with the diagnosis of mild, moderate and severe dysplasia, carcinoma in situ and invasive carcinoma of the cervix, dividing them into three groups: squamous intraepithelial lesion of low grade, high grade and invasive carcinoma. This study was carried out with the infrastructure resources available in the services of Gynecology and Pathology of Belen Hospital and Laboratory of Molecular Biology, of Tropical Medicine Institute at the UNT, where were carried out the polymerase chain reaction testing and the run gel electrophoresis SSCP (single-strand conformational polymorphism). It was found that in patients with invasive carcinoma and high grade squamous intraepithelial lesion (SIL), 93.3% showed the L83V variant of E6 oncoprotein. Likewise, in patients with low grade SIL, 73,3% had the variant. Despite that women with high-grade SIL and cervical carcinoma had the aggressive variant of the virus at higher rates than patients with low grade SIL, this difference was not statistically significant. However, it is not possible to rule out the influence of the variation in the transformation of infected cells to malignancy. These results suggest that it is advisable to conduct larger studies to determine whether the presence of variant plays a major role in malignant transformation of premalignant lesions.